Zero-defect load wave-absorbing material and preparation method thereof
By using a combination of a three-dimensional vibration table and a vacuum oven in a high-viscosity electromagnetic paste, the problem of zero defect molding of high-filling absorbing materials is solved, and the high-performance molding of materials is achieved, meeting the needs of aviation and aerospace products.
Patent Information
- Application Number
- CN202411725579.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art is difficult to achieve zero defect molding of high-filling absorbing materials, especially in high-viscosity slurries, and conventional processes are difficult to effectively remove internal hollow defects.
The combination of a three-dimensional vibration table and a vacuum oven is used to eliminate defects in high viscosity electromagnetic slurry. The specific steps include performing preliminary defect removal on the three-dimensional vibration table, then performing secondary defect removal in a vacuum oven, and finally curing and forming in the mold.
It realizes zero defect molding of high-filled load absorbing materials, improves the overall performance of the material, and can meet the needs of aviation and aerospace products for high-performance load absorbing materials.
Smart Images

Figure CN119613920A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electromagnetic wave absorbing materials, and in particular relates to a zero-defect load absorbing material and a preparation method thereof. Background Art
[0002] Rigid absorbing materials are mainly composed of absorbents, binders and various processing aids. They are multifunctional polymer composite materials with absorbing properties of anti-electromagnetic interference, microwave directional enhancement and clutter suppression. According to their loss mechanism, they can be divided into three categories: resistance type, dielectric type and magnetic dielectric type. The strength of their loss capacity is mainly affected by the absorbent content inside the material. The higher the absorbent content, the stronger their absorbing loss capacity.
[0003] However, the absorbent content cannot be added indefinitely, as it is restricted by the molding process. When the absorbent is added to a certain extent, the absorbent cannot be bonded together by the adhesive, which means that the upper limit of the absorbent addition has been reached. Before the upper limit of the absorbent addition, the more the absorbent content, the greater the viscosity of the slurry after mixing and homogenizing with the adhesive, and the more difficult it is to remove the air trapped inside the slurry during the mixing process. After solidification and molding, there are a large number of void defects inside the material, which makes it difficult to meet the use requirements of various aviation and aerospace products. The current conventional process of vacuum removal of internal bubbles from low-viscosity slurries is not suitable for high-viscosity slurries, making zero-defect molding of high-filling absorbing materials an urgent problem to be solved.
[0004] Therefore, in view of the above material preparation problems, it is necessary to provide a high-filling-loaded absorbing material and a zero-defect molding preparation method to meet the use requirements of various aviation and aerospace products for loaded absorbing materials. Summary of the invention
[0005] The purpose of the present invention is to provide a zero-defect load absorbing material and a preparation method thereof, and to prepare the zero-defect load absorbing material by eliminating defects in the slurry in a vibration and vacuum manner.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows:
[0007] A method for preparing a zero-defect loaded absorbing material comprises the following steps:
[0008] (1) mixing the absorber and the adhesive, and stirring them fully to obtain a high-viscosity electromagnetic slurry;
[0009] (2) High-viscosity electromagnetic slurry is filled into a molding mold, and internal defects of the slurry are eliminated using a three-dimensional vibration table. The slurry is then placed in a vacuum oven for secondary defect elimination. Finally, the treated slurry is cured in the mold to obtain a zero-defect loaded absorbing material.
[0010] Preferably, the mass ratio of the absorbent to the adhesive is 90:(9-10).
[0011] Preferably, the absorber is carbonyl iron powder or alloy powder.
[0012] Preferably, the particle size of the wave absorbing agent is 1-10 μm.
[0013] Preferably, the adhesive is epoxy resin, bismaleimide resin or phenolic resin.
[0014] Preferably, the viscosity of the high-viscosity electromagnetic slurry is 10P·s≤μ≤50P·s.
[0015] Preferably, the vibration frequency of the three-dimensional vibration table is 20-40 Hz.
[0016] Preferably, the vibration time of the three-dimensional vibration table is 5-15 minutes.
[0017] Preferably, the temperature of the vacuum oven is 80-100°C.
[0018] Preferably, the vacuum oven is kept for 30-60 minutes.
[0019] Preferably, the vacuum degree of the vacuum oven is ≤-0.09 MPa.
[0020] A zero-defect loaded absorbing material is prepared by adopting the above preparation method.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects:
[0022] (1) The present invention removes bubbles from high-viscosity slurry by combining the three-dimensional vibration table degassing and vacuum oven degassing processes, thereby achieving zero-defect molding of high-filling load-absorbing materials, which effectively promotes the further improvement of the performance of the load-absorbing materials.
[0023] (2) The necessary condition for the present invention to use a three-dimensional vibration table for debubbling is that the viscosity of the slurry is moderate. Because when low-viscosity slurry (μ<10P·s) is vibrated for debubbling, the high-density metal absorber in the slurry will settle, resulting in phase separation, affecting the overall uniformity of the material. The high-viscosity slurry (10P·s≤μ≤50P·s) system has a large overall viscosity and is not easy to settle, so it is suitable for debubbling using a vibration table. However, it is necessary to study the vibration time, frequency, etc. to avoid a large impact on the overall uniformity of the material due to too long a vibration time or too fast a frequency. For higher viscosity slurries (μ>50P·s), the absorbent accounts for too high a proportion, and the absorbent and the adhesive cannot be effectively dispersed, mixed, and bonded into a whole, and the vibration plasticity is lost, so it is not suitable for debubbling using a three-dimensional vibration table. Therefore, the present invention can greatly reduce the difficulty of eliminating internal defects in the slurry and reduce production costs by limiting the slurry to a suitable viscosity and then using a three-dimensional vibration table.
[0024] (3) The zero-defect load-absorbing material obtained in this application can meet the demand for high-performance load-absorbing materials for aviation and aerospace products. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a CT test image of the zero-defect loaded absorbing material of Example 1;
[0026] Figure 2 It is a schematic diagram of the overall electromagnetic uniformity test sampling of the loaded absorbing material.
[0027] Figure 3 This is a physical photo of the zero-defect loaded absorbing material of Comparative Example 1.
[0028] Figure 4 This is the CT inspection image of the defective load absorbing material of Comparative Example 3.
[0029] Figure 5 This is the CT inspection picture of the defective load absorbing material of Comparative Example 4.
[0030] Figure 6 This is the CT inspection image of the defective load absorbing material of Comparative Example 5. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The present invention provides a high-filling-loaded absorbing material and a zero-defect molding preparation method. The preparation method comprises the following steps:
[0033] (1) Mixing the absorber and the adhesive in a certain proportion and stirring them fully to obtain a high-viscosity electromagnetic slurry;
[0034] (2) The mixed and homogenized slurry is filled into a molding mold, and a three-dimensional vibration table is used to eliminate internal defects of the slurry at a certain vibration frequency and time. The slurry is then placed in a vacuum oven and secondary defects are eliminated at a certain temperature, vacuum degree and time. Finally, the treated slurry is cured in the mold to obtain a zero-defect load-absorbing material, and an industrial CT and electromagnetic parameter testing system are used for non-destructive testing of the material and uniformity verification.
[0035] In a preferred embodiment, the mass ratio of the absorbent to the adhesive is 90:(9-10) (for example, it may be 90:9, 90:9.5 or 90:10).
[0036] According to some preferred embodiments, the particle size of the absorbent is 1-10 μm (for example, it may be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm).
[0037] According to some preferred embodiments, the absorber is carbonyl iron powder or alloy powder.
[0038] According to some preferred embodiments, the resin is an epoxy resin, a bismaleimide resin or a phenolic resin.
[0039] According to some preferred embodiments, the viscosity of the high-viscosity electromagnetic slurry is 10P·s≤μ≤50P·s (for example, it may be 10P·s, 20P·s, 30P·s, 40P·s or 50P·s).
[0040] According to some preferred embodiments, the vibration frequency of the three-dimensional vibration table is 20-40 Hz (for example, it may be 20 Hz, 30 Hz or 40 Hz).
[0041] According to some preferred embodiments, the vibration time of the three-dimensional vibration table is 5-15 minutes (for example, it can be 5 minutes, 10 minutes or 15 minutes).
[0042] According to some preferred embodiments, the temperature of the vacuum oven is 80-100°C.
[0043] According to some preferred embodiments, the vacuum oven is kept for 30-60 minutes.
[0044] According to some preferred embodiments, the vacuum degree of the vacuum oven is ≤-0.09 MPa.
[0045] In order to more clearly illustrate the technical solution and advantages of the present invention, a high-filling-loaded absorbing material and a zero-defect molding preparation method are described in detail below through several embodiments.
[0046] Example 1
[0047] (1) 900 g of carbonyl iron powder (particle size 5 μm) and 100 g of epoxy resin were placed in a planetary stirrer and homogenized to obtain a high-viscosity electromagnetic slurry with a slurry viscosity of 10 P·s;
[0048] (2) The mixed and homogenized slurry is filled into a molding mold, and a three-dimensional vibration table is used to vibrate the slurry at a vibration frequency of 20 Hz for 10 minutes to eliminate internal defects of the slurry. The slurry is then placed in a vacuum oven and treated at 100°C and -0.095 MPa for 30 minutes. Finally, the treated slurry is cured in the mold to obtain a zero-defect load-absorbing material.
[0049] Example 2
[0050] Example 2 is basically the same as Example 1, except that the mass ratio of the absorbent to the adhesive is 90:9, that is, 900 g of carbonyl iron powder and 90 g of epoxy resin, and the slurry viscosity is 50 P·s.
[0051] Example 3
[0052] Example 3 is substantially the same as Example 1, except that the particle size of the carbonyl iron powder is 10 μm.
[0053] Example 4
[0054] Example 4 is substantially the same as Example 1, except that the resin adhesive is bismaleimide resin and the slurry viscosity is 30 P·s.
[0055] Example 5
[0056] Example 5 is basically the same as Example 1, except that the vibration frequency of the three-dimensional vibration table is 40 Hz.
[0057] Example 6
[0058] Example 6 is basically the same as Example 1, except that the vibration time of the three-dimensional vibration table is 15 minutes.
[0059] Example 7
[0060] Example 7 is substantially the same as Example 1, except that the temperature of the vacuum oven is 80°C.
[0061] Example 8
[0062] Example 8 is basically the same as Example 1, except that the vacuum degree of the vacuum oven is -0.090 MPa.
[0063] Example 9
[0064] Example 9 is basically the same as Example 1, except that the vacuum oven treatment time is 60 minutes.
[0065] Comparative Example 1
[0066] (1) 700 g of carbonyl iron powder (particle size 5 μm) and 300 g of epoxy resin were placed in a planetary stirrer and homogenized to obtain a high-viscosity electromagnetic slurry;
[0067] (2) The mixed and homogenized slurry is filled into a molding mold, and a three-dimensional vibration table is used to vibrate the slurry at a vibration frequency of 20 Hz for 10 minutes to eliminate internal defects of the slurry. The slurry is then placed in a vacuum oven and treated at 100°C and -0.095 MPa for 30 minutes. Finally, the treated slurry is cured in the mold to obtain a loaded absorbing material.
[0068] Comparative Example 2
[0069] (1) 900 g of carbonyl iron powder (particle size 20 μm) and 100 g of epoxy resin were placed in a planetary stirrer and homogenized to obtain a high-viscosity electromagnetic slurry;
[0070] (2) The mixed and homogenized slurry is filled into a molding mold, and a three-dimensional vibration table is used to vibrate the slurry at a vibration frequency of 20 Hz for 10 minutes to eliminate internal defects of the slurry. The slurry is then placed in a vacuum oven and treated at 100°C and -0.095 MPa for 30 minutes. Finally, the treated slurry is cured in the mold to obtain a loaded absorbing material.
[0071] Comparative Example 3
[0072] (1) 900 g of carbonyl iron powder (particle size 5 μm) and 100 g of epoxy resin were placed in a planetary stirrer and homogenized to obtain a high-viscosity electromagnetic slurry;
[0073] (2) The mixed and homogenized slurry is filled into a molding mold, and a three-dimensional vibration table is used to vibrate the slurry at a vibration frequency of 10 Hz for 10 minutes to eliminate internal defects of the slurry. The slurry is then placed in a vacuum oven and treated at 100°C and -0.095 MPa for 30 minutes. Finally, the treated slurry is cured in the mold to obtain a loaded absorbing material.
[0074] Comparative Example 4
[0075] (1) 900 g of carbonyl iron powder (particle size 5 μm) and 100 g of epoxy resin were placed in a planetary stirrer and homogenized to obtain a high-viscosity electromagnetic slurry;
[0076] (2) The mixed and homogenized slurry is filled into a molding mold, and a three-dimensional vibration table is used to vibrate the slurry at a vibration frequency of 20 Hz for 30 minutes to eliminate internal defects of the slurry. The slurry is then placed in a vacuum oven and treated at 100°C and -0.095 MPa for 30 minutes. Finally, the treated slurry is cured in the mold to obtain a loaded absorbing material.
[0077] Comparative Example 5
[0078] (1) 900 g of carbonyl iron powder (particle size 5 μm) and 100 g of epoxy resin were placed in a planetary stirrer and homogenized to obtain a high-viscosity electromagnetic slurry;
[0079] (2) The mixed and homogenized slurry is filled into a molding mold, and then placed in a vacuum oven and treated at 100° C. and −0.095 MPa for 30 min. Finally, the treated slurry is cured in the mold to obtain a loaded absorbing material.
[0080] Comparative Example 6
[0081] (1) 900 g of carbonyl iron powder (particle size 5 μm) and 60 g of epoxy resin were placed in a planetary mixer for homogenization and mixing. The carbonyl iron powder and the epoxy resin could not be effectively dispersed, mixed, or bonded into a whole.
[0082] (2) The slurry obtained above is filled into a molding mold. Since the viscosity of the slurry is too high, it loses its vibration plasticity and cannot be used to prepare a zero-defect load absorbing material through this molding process.
[0083] The load absorbing materials obtained in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 5 were respectively inspected for internal defects using industrial CT, and the defect-free products ( Figure 1 ) The material uniformity test was carried out according to a certain sampling method (the dispersion coefficient ≤ 10% is considered as small dispersion). The specific test is as follows: Figure 2 A single piece of material was sampled and machined into a waveguide specimen according to the standard. The complex dielectric parameters ε', ε" and magnetic permeabilities μ', μ" were measured at different frequencies in the range of 2.6-3.95 GHz by a vector grid analyzer, and the dispersion coefficients were calculated. The specific results are shown in Table 1.
[0084] Table 1 Electromagnetic uniformity sampling mechanical properties test results
[0085]
[0086] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a zero-defect loaded absorbing material, characterized in that: The steps include: (1) mixing the absorber and the adhesive, and stirring them fully to obtain a high-viscosity electromagnetic slurry; (2) High-viscosity electromagnetic slurry is filled into a molding mold, and internal defects of the slurry are eliminated using a three-dimensional vibration table. The slurry is then placed in a vacuum oven for secondary defect elimination. Finally, the treated slurry is cured in the mold to obtain a zero-defect loaded absorbing material.
2. The preparation method according to claim 1, characterized in that The mass ratio of the absorbent to the adhesive is 90:(9-10).
3. The preparation method according to claim 1, characterized in that: The wave absorbing agent is carbonyl iron powder or alloy powder.
4. The preparation method according to claim 3, characterized in that: The particle size of the wave absorbing agent is 1-10 μm.
5. The preparation method according to claim 1, characterized in that: The adhesive is epoxy resin, bismaleimide resin or phenolic resin.
6. The preparation method according to claim 1, characterized in that: The viscosity of the high-viscosity electromagnetic slurry is 10P·s≤μ≤50P·s.
7. The preparation method according to claim 1, characterized in that: The vibration frequency of the three-dimensional vibration table is 20-40 Hz, and the vibration time is 5-15 minutes.
8. The preparation method according to claim 1, characterized in that: The temperature of the vacuum oven is 80-100° C., and the time is 30-60 minutes.
9. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum oven is ≤-0.09MPa.
10. A zero-defect loaded absorbing material, characterized in that: The preparation method is described in any one of claims 1 to 9.
Citation Information
Patent Citations
Wave-absorbing honeycomb / rigid foam composite material and preparation method thereof
CN112126114A
Embedded co-cured composite material with large-damping and electromagnetic wave absorbing properties and preparation method and application thereof
US20200376798A1
Cited By
Hot-melt prepreg with low-frequency wave-absorbing performance as well as preparation and application of hot-melt prepreg
CN121427252A
A hot melt prepreg with low-frequency wave absorbing performance and preparation and application thereof
CN121427252B